PKM OPTIMALISASI PERAN BIOKONTROL DALAM BUDIDAYA HORTIKULTURA - PELATIHAN UNTUK PETANI DAN PENYULUH DI LAHAN BASAH - Aidawati, Noor; Sepe, Muslimin; Liestiany, Elly; Abbas, Saipul; Matondang, Putri (BAKIRA: Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service Program (PkM) aims to enhance the understanding and skills of farmers and agricultural extension workers in optimizing the role of biocontrol agents in horticultural cultivation on wetland areas. The activities were carried out through training sessions, field practices, and technical assistance. The training materials covered the identification of various types of biocontrol agents, application techniques, and their benefits in reducing the use of chemical pesticides. Evaluation results indicated a significant increase in participants’ knowledge levels, as well as a positive shift in attitudes toward the adoption of more environmentally friendly biological control methods. Moreover, the application of biocontrol agents in demonstration plots showed healthier plant growth with minimal pest attacks. This program is expected to serve as an initial step towards promoting sustainable horticultural cultivation practices in wetland areas.